20‐Hydroxyecdysone regulates the prophenoloxidase cascade to immunize Metarhizium anisopliae in Locusta migratoria. Issue 9 (7th May 2020) - Han, Pengfei; Gong, Qitian; Fan, Jiqiao; Zhang, Min; Abbas, Mureed; Zhu, Wenya; Deng, Sufang; Xing, Shuping; Zhang, Jianzhen
Abstract: BACKGROUND: PPO (prophenoloxidase) cascade plays an important role in resisting invasion of entomogenous fungus. The 20‐hydroxyecdysone (20E) exerts potent effect on the innate immunity in many insects. However, whether 20E controls the PPO cascade system against fungi and the regulatory mechanism in insects remains unclear. RESULTS: In this study, both the proteome and transcriptome of Locusta migratoria were determined followed by the induction of 20E. Pattern recognition receptor GNBP‐2 (Gram‐negative binding proteins) has been identified that responded to 20E at both messenger RNA (mRNA) and protein levels. The PPO gene expression in fat body and PO (phenoloxidase) activity in plasma was found significantly induced after 20E injection and during the high‐20E developmental stage. However, when 20E signal was blocked by RNA interference (RNAi) of ecdysone receptor, the expression level of PPO and PO activity failed to be increased by 20E. Thus, 20E could not significantly induce the expression of PPO gene and PO activity after RNAi of GNBP‐2. Furthermore, 20E treatment notably enhanced the resistance of L. migratoria against Metarhizium anisopliae . Followed by of GNBP‐2 silencing, the mortality of nymphs was significantly increased under the stress of Metarhizium anisopliae, and 20E injection could not increase the resistance. CONCLUSION: The 20E regulates the PPO system to resist fungal invasion via regulating GNBP‐2 in worldwide pest L. migratoria . Our results provide insight into the mechanism of how 20E enhances the antimicrobial immunity, and will be beneficial for modification of entomogenous fungi targeting on hormones and the immune system. © 2020 Society of Chemical Industry Abstract : Insect immune response blocks the invasion of entomogenous fungi. This study demonstrated that 20‐hydroxyecdysone (20E) regulated the prophenoloxidase cascade to resist pathogenetic fungi via regulating GNBP‐2 in Locusta migratoria .